2019
DOI: 10.3390/ijms20071721
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin Receptor-1 Expression in Human Prostate Cancer: A Pilot Study on Primary Tumors and Lymph Node Metastases

Abstract: Neurotensin and its high-affinity receptor, NTR1, are involved in the growth of various tumors. Few data are available regarding NTR1 expression in normal and tumoral human prostate tissue samples. NTR1 expression was assessed using immunohistochemistry in 12 normal prostate tissues, 11 benign prostatic hyperplasia (BPH), 44 prostate cancers, and 15 related metastatic lymph nodes (one per patient, when available). NTR1-staining was negative in normal prostate and BPH samples. NTR1 was overexpressed in four out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
(49 reference statements)
1
25
0
Order By: Relevance
“…A more recent study, studying the NTSR1 expression in normal, benign prostatic hyperplasia (BPH), prostatic cancer and metastatic lymph nodes, there was no clear association between NTSR1 and age, PSA values, Gleason score, pathological T stage, but there was more frequent NTSR1 overexpression in metastatic lymph nodes compared to primary tumours (p = 0.038) [49]. The authors concluded, in this study, that this may open a new perspective in imaging and radionuclide therapy in prostate cancer [49].…”
Section: Prostate Cancermentioning
confidence: 99%
“…A more recent study, studying the NTSR1 expression in normal, benign prostatic hyperplasia (BPH), prostatic cancer and metastatic lymph nodes, there was no clear association between NTSR1 and age, PSA values, Gleason score, pathological T stage, but there was more frequent NTSR1 overexpression in metastatic lymph nodes compared to primary tumours (p = 0.038) [49]. The authors concluded, in this study, that this may open a new perspective in imaging and radionuclide therapy in prostate cancer [49].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Accordingly, the neurotensin subtype 1 receptor (NTS1R) [7,8] has been regarded as an attractive molecular target for such purposes owing to its high density expression in many human cancers [9,10]. Thus, high NTS1R expression has been documented in pancreatic ductal adenocarcinoma [11][12][13], Ewing's sarcoma [14], colon carcinoma [15], prostate [16] and breast cancer [17], as well as other cancer types [18]. This finding offers the opportunity to develop theranostic NTS1R-directed radioligands based on the native tridecapeptide neurotensin (NT) for oncological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The neurotensin subtype 1 receptor (NTS1R) has been regarded as a valid biomolecular target in cancer theranostics, owing to its high-density expression in a variety of human tumors, such as pancreatic ductal adenocarcinoma (PDAC), colon carcinoma, Ewing's sarcoma, or prostate and breast cancer [1][2][3][4][5][6][7][8][9][10][11][12]. This overexpression can be elegantly exploited to direct NTS1R-seeking radionuclide carriers to tumor sites [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This overexpression can be elegantly exploited to direct NTS1R-seeking radionuclide carriers to tumor sites [13,14]. Typically, radiolabeled analogs of the C-terminal hexapeptide fragment of neurotensin (NT = Pyr-Leu-Tyr-Glu-Asn-Lys-Pro-Arg-Arg-Pro-Tyr-Ile-Leu-OH), NT (8)(9)(10)(11)(12)(13), have been considered for such purposes [15][16][17][18][19][20][21][22][23][24]. For stable binding of metal radionuclides, a suitable Int.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation